Sense Relations Analysis on Ed Sheeran’s Equals Album: A Semantics Study - Jordan Angga Kusuma; Ervina CM Simatupang (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This study aimed to analyze the sense relations and their type of word meanings that found on Ed Sheeran’s Equals Album. The method used in this study was descriptive qualitative method. Data sources were taken from the song lyrics of the latest Ed Sheeran’s album. Some of the meaning words were taken from Cambridge Dictionary and Meriam Webster. The theories used to analyze the data were from Hurford and Heasley theory (1986) and Richard and Schmidt theory (2002). The result of this analysis that there were 5 types of sense relation found on this album. They were synonymy 32.3%, polysemy 10.8%, hyponymy 12.3%, homonymy 9.2%, and antonymy 35.4%. This research inferred that synonymy was the most prevalent of the sense relations found in Ed Sheeran's songs from the album Equals. Antonymy accounted for 35.4% of the total, whereas the other types were lower. The second most common form was synonymy, which accounted for up to 32.3%, followed by polysemy and hyponymy, which accounted for 23.1%. Homonymy was the lowest proportion of up to 9.2%.